Polyhexanide as a new antiseptic composition for a dentist - Z. S. Khabadze; D. S. Nazarova; A. A. Kulikova; Yu. A. Generalova; E. S. Shilyaeva; A. P. Kotelnikova (LLC "Endo Press", 2021)
Aim. To assess systematically the available scientific evidence about clinical response of using polyhexanide as an antiseptic agent in medicine and dentistry. The properties of polyhexanide - excellent antimicrobial activity, chemical stability and low toxicity - have been studied.